Effect of cold oxygen plasma treatment on mechanical properties of phenylenebenzobisoxazole fiber-filled cross-linked polyethylene composites. (July 2016) - Tang, G; Hu, X; Li, XL; Shao, Ch. zh.; Tang, TH
Mechanical strength of phenylenebenzobisoxazole (PBO) fibers and cross-linked polyethylene (XLPE) matrix composites were studied with particular interest on the effects of oxygen cold plasma-treated fibers. PBO fibers were treated in a radio frequency plasma reactor using oxygen for different treatment times to increase the interface adhesion. Tensile tests on PBO fibers showed that plasma treatment caused an increase in average tensile strength compared with untreated fibers. Fracture analysis confirmed the increase in interfacial adhesion due to oxygen plasma treatment.